2023
DOI: 10.3390/pharmaceutics15030885
|View full text |Cite
|
Sign up to set email alerts
|

Development of the 99mTc-Labelled SST2 Antagonist TECANT-1 for a First-in-Man Multicentre Clinical Study

Abstract: Broad availability and cost-effectiveness of 99Mo/99mTc generators worldwide support the use, and thus the development, of novel 99mTc-labelled radiopharmaceuticals. In recent years, preclinical and clinical developments for neuroendocrine neoplasms patient management focused on somatostatin receptor subtype 2 (SST2) antagonists, mainly due to their superiority in SST2-tumour targeting and improved diagnostic sensitivity over agonists. The goal of this work was to provide a reliable method for facile preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A very interesting paper (Opalinska et al 2023 ) recently reported a new advancement for imaging neuroendocrine tumours (NET) with a novel 99m Tc-radiolabelled somatostatin receptor (SSTR) antagonist ([ 99m Tc]Tc-TECANT1) (Novak et al 2023 ). The current standard for imaging NET is the SSTR agonist [ 68 Ga]Ga-DOTA-TATE/TOC.…”
Section: Are New Radiopharmaceuticals Making Nuclear Medicine Still U...mentioning
confidence: 99%
“…A very interesting paper (Opalinska et al 2023 ) recently reported a new advancement for imaging neuroendocrine tumours (NET) with a novel 99m Tc-radiolabelled somatostatin receptor (SSTR) antagonist ([ 99m Tc]Tc-TECANT1) (Novak et al 2023 ). The current standard for imaging NET is the SSTR agonist [ 68 Ga]Ga-DOTA-TATE/TOC.…”
Section: Are New Radiopharmaceuticals Making Nuclear Medicine Still U...mentioning
confidence: 99%
“…Below (Fig. 1), we present a comparison of SPECT/CT with a SSTR antagonist [ 99m Tc]Tc-TECANT1 (N4-p-Cl-Phe-cyclo(D-Cys-Tyr-D-Aph(Cbm)-Lys-Thr-Cys)-D-Tyr-NH2, where D-Aph(Cbm): D-4-amino-carbamoyl-phenylalanine) [ 3 ] and [ 68 Ga]Ga-DOTA-TATE PET/CT (EudraCT no 2019–003379-20). Please note better visualization of the lesions seen in the study with [ 99m Tc]Tc-TECANT1 (in 6 out of 7 lesions) as well as significantly higher tumor-to-background ratio (in primary and metastatic lesions) obtained with the novel tracer (measured as an absolute number of counts in lesion to background (TBR)) in comparison to [ 68 Ga]Ga-DOTA-TATE PET/CT (4,07 (range 1,36–7,58) vs 2,26 (range 1,15–3,39)).…”
mentioning
confidence: 99%